Intrapallidal injection of cannabidiol or a selective GPR55 antagonist decreases motor asymmetry and improves fine motor skills in hemiparkinsonian rats - Patricio, Felipe; Morales Dávila, Eliud; Patricio-Martínez, Aleidy; Arana Del Carmen, Nayeli; Martínez, Isabel; Aguilera, José; Perez-Aguilar, Jose Manuel; Limón, Ilhuicamina Daniel (Frontiers in Pharmacology, 2022)
Recently, the GPR55 receptor has emerged as a molecular target of CBD. Interestingly, GPR55 mRNA is expressed in the GPe and striatum, hence, it has been suggested that its activity is linked to motor dysfunction in PD. The present study aimed to evaluate the effect of the intrapallidal injection of both CBD and a selective GPR55 antagonist (CID16020046) on the motor asymmetry and fine motor skills of hemiparkinsonian rats. The hemiparkinsonian animal model applied involved the induction of a lesion in male Wistar rats via the infusion of the neurotoxin 6-OHDA into the medial forebrain bundle via stereotaxic surgery. After a period of twenty days, a second surgical procedure was performed to implant a guide cannula into the GPe. Seven days later, lysophosphatidylinositol(LPI), CBD, or CID16020046 were injected for three consecutive days (from the 28th to the 30th day post-lesion). Amphetamine-induced turning behavior was evaluated on the 14th and 30th days post-injury. The staircase test and fine motor skills were evaluated as follows: the rats were subject to a ten-day training period prior to the 6-OHDA injury; from the 15th to the 19th days post-lesion, the motor skills alterations were evaluated under basal conditions; and, from the 28th to the 30th days post-lesion the pharmacological effects of the drugs administered were evaluated. The results obtained show that the administration of LPI or CBD generated lower levels of motor asymmetry in the turning behavior of hemiparkinsonian rats. It was also found that the injection of CBD or CID16020046, but not LPI, into the hemiparkinsonian rats generated significantly superior performance, in the staircase-test, in the use of the forelimb contralateral to the 6-OHDA-induced lesion. Finally, superior fine motor skills were observed for the following movements in the hemiparkinsonian rats treated with CBD or CID16020046 when evaluated from the 28th to the 30th days post-lesion: pronation; grasp; and, supination. The results obtained suggest that the inhibitory effects of CBD and CID16020046 on GPR55 in the GPe could be related to GABAergic overactivation in hemiparkinsonism, thus opening new perspectives to explain, at a cellular level, the reversal of motor impairment observed in PD models.